METHODS OF FINANCING INVESTMENT PROJECTS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores various methods of financing investment projects, analyzing their characteristics, advantages, and limitations. It provides a comprehensive overview of traditional and modern financing approaches, including equity financing, debt financing, venture capital, crowdfunding, and public-private partnerships. Through a systematic literature review and analysis, the study identifies the suitability of each method for different project types and economic contexts. The findings offer practical insights for project managers and investors seeking optimal financing strategies.